2022
DOI: 10.1088/1361-665x/ac60b5
|View full text |Cite
|
Sign up to set email alerts
|

4D printed shape memory sandwich structures: experimental analysis and numerical modeling

Abstract: Additive manufacturing has provided a unique opportunity to fabricate highly complex structures as well as sandwich structures with various out-of-plane cores. The application of intelligent materials, such as shape memory polymers, gives an additional dimension to the three-dimensional (3D) printing process, known as four-dimensional (4D) printing, so that the deformed structures can return to their initial shape by the influence of an external stimulus like temperature. In this study, 4D printing of smart sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…By comparing the sandwich structures with reentrant and honeycomb core designs, it should be highlighted that the reentrant core absorbed more energy than the honeycomb core. One of the main reasons is that the inner density of the core in the reentrant was higher than in the honeycomb core design [13]. Moreover, SEA was increased from PLA to PETG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the sandwich structures with reentrant and honeycomb core designs, it should be highlighted that the reentrant core absorbed more energy than the honeycomb core. One of the main reasons is that the inner density of the core in the reentrant was higher than in the honeycomb core design [13]. Moreover, SEA was increased from PLA to PETG.…”
Section: Resultsmentioning
confidence: 99%
“…Specific energy absorption (SEA) is a significant measure for assessing the energy absorption of sandwich structures. It is defined as the sandwich structures' unit energy absorption efficiency, expressed as [13]: The overall trend in Table 2 showed that higher specific energy absorption were obtained in the reentrant sandwich structures compared to honeycomb sandwich structures. By comparing the sandwich structures with reentrant and honeycomb core designs, it should be highlighted that the reentrant core absorbed more energy than the honeycomb core.…”
Section: Resultsmentioning
confidence: 99%
“…The area under the load–displacement curve also illustrates the applied energy to the sandwich structures by compressive loading. [ 32 ] In particular, the energy a sandwich structure absorbs during loading is generated by two separate mechanisms: i) absorbed energy due to elastic deformation; ii) dissipated energy as a result of plastic deformation. The total energy, defined by the area under the plot, shows that the origami structures have better energy absorption (22.1 J) as compared to the chiral structures (19.4 J); hence, the following analysis will focus solely on the origami structures.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they have looked into how 4D-printed sandwich structures could be used for energy absorption applications. [40] The literature review discloses the importance of 3D energy absorbers to exhibit low initial reaction forces, stability, and high energy absorption capacity under quasistatic compression. The current study introduces novel 3D ZPR metamaterials for reversible energy absorption applications additively manufactured by 4D printing technology.…”
Section: Doi: 101002/adem202200656mentioning
confidence: 99%
“…In addition, they have looked into how 4D‐printed sandwich structures could be used for energy absorption applications. [ 40 ]…”
Section: Introductionmentioning
confidence: 99%